Production of activated charcoal from sugarcane bagasse using physical activation - Mella Yolanda Alfika; Ety Jumiati; Miftahul Husnah (Indonesian Physics Communication, 2024)
Activated carbon is a material containing 85% – 95% carbon elements and is a porous solid. This activated carbon is the result of heating materials containing carbon at high temperatures but not oxidized. In this study, the material used is sugarcane bagasse, and its activator is NaOH. The purpose of this research is to examine the production of Activated Carbon from Sugarcane Bagasse with different concentrations of NaOH activator, analyze the moisture content, ash content, volatile matter content, and fixed carbon content. Carbonization is carried out using a furnace at a temperature of 500°C for 1 hour. Carbon activation is done using NaOH solution with concentrations of 0.3%, 0.5%, and 0.7%. Irradiation is done using a microwave with a power of 630 Watts for 20 minutes. The results of this study indicate that the NaOH concentration affects some characteristics of the activated charcoal produced from sugarcane bagasse. A NaOH concentration of 0.7% produces activated charcoal with the best characteristics, with a moisture content of 3.1%, volatile matter content of 20.4%, total ash content of 5.9%, and carbon content of 62.2%.